2017
DOI: 10.3390/coatings7110193
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis and Electrophoretic Deposition of NiO/Ni Core-Shell Nanoparticles and Its Application as Pseudocapacitor

Abstract: A simple, low cost and transferable colloidal processing method and the subsequent heat treatment has been optimized to prepare binder-free electrodes for their application in supercapacitors. NiO/Ni core-shell hybrid nanostructures have been synthetized by heterogeneous precipitation of metallic Ni nanospheres onto NiO nanoplatelets as seed surfaces. The electrophoretic deposition (EPD) has been used to shape the electroactive material onto 3D substrates such as Ni foams. The method has allowed us to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The synthesis was made by mixing 8 mmol of nickel nitrate hexahydrated (Ni(NO 3 ) 2 , 99.9% purity; Panreac, Spain), and 40 mmol of ammonia (NH 3 , 28%, Panreac, Spain) in a total volume of 80 ml of aqueous solution. This procedure was previously described more in detail elsewhere [10,31,35].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis was made by mixing 8 mmol of nickel nitrate hexahydrated (Ni(NO 3 ) 2 , 99.9% purity; Panreac, Spain), and 40 mmol of ammonia (NH 3 , 28%, Panreac, Spain) in a total volume of 80 ml of aqueous solution. This procedure was previously described more in detail elsewhere [10,31,35].…”
Section: Methodsmentioning
confidence: 99%
“…The development of hybrid capacitors may result in a superior performance since both storage energy phenomena (ionic double layer and redox reactions) take place at the same time [8,9]. Among all the transition metal oxides, NiO is consider a promising candidate in the manufacturing of supercapacitors due to their high theoretical specific capacitance (3750 F/g), chemical and thermal stability and low cost [10,11]. However, it presents some common drawbacks of the semiconductor materials since delivers poor reversibility at the chargedischarge process due to the volumetric alteration of the crystalline structure during the redox reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values, revealing high energy storage capacities, are much higher than previously reported values on Ni based energy storage materials [1,11]. For example, Joaquin et al reported 755 Fg −1 at 1 Ag −1 on electrophoretic deposited core shell nanowire arrays of Ni/NiO [12] while Navale et al reported 458 Fg −1 at 1 Ag −1 corresponding to potentiostatic electrodeposited NiO thin films on stainless steel [11]. However, Farrukh et al have previously reported a similar high capacitance value of 2093 F/g on their NiO nanotubes electrochemically deposited on anodized aluminium (AAO) [13].…”
Section: Resultsmentioning
confidence: 70%
“…The pseudocapacitor electrochemical behavior of as-prepared electrodes was determined by Electrochemical Impedance Spectroscopy (EIS) in order to determine charge transfer between the active material (NiO) and the collector (substrate) in EPD electrodes. [9]…”
Section: Introductionmentioning
confidence: 99%